PENGARUH KOMPRES REBUSAN JAHE TERHADAP NYERI LUTUT PADA LANSIA DI PANTI SOSIAL KHUSNUL KHOTIMAH PEKANBARU - een husanah; Rika Andriyani (Jurnal Ilmu Kebidanan, 2019)
The knee is the main joint to support the body's weight. The stability of the work of this joint depends on the muscles and ligaments around it. Muscular strength begins to decline around the age of 40 with an accelerated setback after 60 years. The main signs of a musculoskeletal system disorder are pain and discomfort, which can vary from the mildest to the most severe. The results of interviews with 10 elderly people who had knee pain, found 7 elderly people using pharmaceutical drugs, 3 people did not consume certain drugs. Of the 7 elderly who use drugs, they often feel the side effects of medications taken such as nausea and diarrhea and feel the effects of dependence. This type of research is pre-experimental research with pre-test and post-test design using a quantitative research approach with design Quasi in one group (one group pre-posttest design) to determine the strength of the influence of ginger compresses on the intensity of knee pain. The research method made direct observations to respondents by filling in the observation sheets of pain intensity pretest and posttest with numerical pain intensity scale (0-10). Research data were analyzed using Wilcoxon signed rank test. The results showed that the average (mean) pain intensity before being given a ginger compress was 4.56 with a standard deviation of 1.381. The mean (intensity) pain intensity after being given a ginger compress is 2.89 with a standard deviation of 1.451. From the results of the statistical test p value (α) of 0,000, that there is an effect of ginger compresses with knee pain in the elderly.